Chemical and physical processes caused by electrons impacting on H2O–CO mixed ices. Issue 2 (6th October 2022) - Huang, C-H; Cecchi-Pestellini, C; Ciaravella, A; Jiménez-Escobar, A; Hsiao, L-C; Sie, N-E; Chen, Y-J
ABSTRACT: Electron-induced chemistry is relevant to many processes that occur when an ionizing source interacts with matter, as in the formation of complex molecules within frozen condensates in space. We explore in this paper the radiolysis and the desorption processes affecting iced mixtures of water and carbon monoxide subjected to electron irradiation in the sub-keV regime. The experiments have been performed with the Interstellar Energetic Process System (IEPS), an ultra-high vacuum chamber equipped with an electron gun. The irradiated ices have been monitored with infrared and mass spectroscopies. We derive the chemistry and determine cross-sections for relevant processes as functions of the energy of the impacting electrons. We quantify the electron-stimulated desorption of some significant species in terms of their desorption yields, and relate these quantities to the electron penetration depth and the desorption-relevant length. The results of this study have been compared with the outcomes of similar experiments performed using pure carbon monoxide ices.